The rules of play : national identity and the shaping of Japanese leisure - Leheny, David Richard, 1967- (Cornell studies in political economy., 2003)
"The Japanese government seeks to influence the use of leisure time to a degree that Americans and Europeans would likely find puzzling. Through tourism-promotion initiatives, financing for resort development, and systematic research on recreational practices, the government takes a relentless interest in its citizens' "free time." David Leheny argues that material interests are not a sufficient explanation for such a large and consistent commitment of resources. In The Rules of Play, he reveals the link between Japan's leisure politics and its long-term struggle over national identity."